Astrofizika z nevtrini - poskus Ice Cube - Vodeb, Veronika (Matrika, 2016)
This article presents the Ice Cube experiment, that is being carried out on the south pole and is used for detection of neutrinos that arrive to Earth from space. First a short history of neutrno discovery is presented, followed by information about how the experiment works, describing the process of construction and going through the results of the experiment. At the end new experiments that are planned for the future in this field are described.
Keywords: astrofizika; astrophysics; Cherenkov radiation; detektorji delcev; Ice Cube experiment; neutrinos; nevtrini; particle detectors; poskus Ice Cube; sevanje Čerenkova